Tectonic In Architecture - Al-Khafaji, Ali Mohsen (Iraqi Journal of Architecture and Planning, 2018)
Architectural development along its history reflects advancement of expression ability of ideas , elements and structural systems . This explain how a specific structural system gains specific aesthetic values which obtained by cumulative experts advice about construction and architecture , also explain the convertibility of constructional thought pure structural system into structural system tectonic . The research problem was the lake of knowledge about complex degree of tectonic consept and its correlation with the structural system and construction . From this point, the comprehensive understanding of a tectonic concept depends on understanding the essential nature of structural system and construction as long as with functional space (closed and semi - closed) and gets through with functional structure and aesthetical needs without omitting the ethical role in composing architectural and structural coherence which is the main research aim . The research methodology consist of three stages ; First, construct operational definition of tectonic concept. Second, investigate about â€œ Tectonics â€ as â€œ Tectonic construction â€ throughout two levels ; first descriptive concern with corporeal , physical , formal characteristics and the second analytical /descriptive concern with incorporeal, aesthetical, ethical, in the last level it was analyzed many projects depending on main concepts deduct from previous knowledge . The final stage are determines the main research conclusions . Key words : tectonic, form, force, construction, space, aesthetical, ethical .